2010
DOI: 10.4085/1062-6050-45.6.594
|View full text |Cite
|
Sign up to set email alerts
|

Core-Temperature Sensor Ingestion Timing and Measurement Variability

Abstract: Context: Telemetric core-temperature monitoring is becoming more widely used as a noninvasive means of monitoring core temperature during athletic events.Objective: To determine the effects of sensor ingestion timing on serial measures of core temperature during continuous exercise.Design: Crossover study. Setting: Outdoor dirt track at an average ambient temperature of 4.46C 6 4.16C and relative humidity of 74.1% 6 11.0%.Patients or Other Participants: Seven healthy, active participants (3 men, 4 women; age 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 15 publications
1
34
0
Order By: Relevance
“…Physiological studies of heat strain using an ingestible sensor have been conducted on workers from many different occupations, such as coal mining, sports and fire-fighting (34-38), but not on farmworkers. The CHIPS study is the first to conduct comprehensive physiological monitoring of heat strain in Latino farmworkers in the USA.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological studies of heat strain using an ingestible sensor have been conducted on workers from many different occupations, such as coal mining, sports and fire-fighting (34-38), but not on farmworkers. The CHIPS study is the first to conduct comprehensive physiological monitoring of heat strain in Latino farmworkers in the USA.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Domitrovich et al (2010) has shown that there were no significant differences between two gastro-intestinal pills ingested by the same participant 24 hours, and 40 minutes prior to measurements.…”
Section: Methodsmentioning
confidence: 99%
“…It is likely that the ingestible pill transmitted stomach temperature during the initial stages of the exercise. Domitrovich et al 14 demonstrated the validity of pill consumption 40 minutes prior to monitoring albeit in the absence of fluid consumption. While cold water (5 to 8 °C) consumption detrimentally influences T gi accuracy, 15 this potential confounder was minimized by storage of bottled water in ambient conditions that limited the gradient between T gi and water temperature.…”
Section: Methodsmentioning
confidence: 99%